Protective performance assessment of armour structures - Keck, Jeremy Shin Foo (2014)
This report describes the working experience during my industrial attachment with TL@NTU. During the attachment, I was tasked with the responsibility of developing a methodology that involves ballistic penetration on body armour testing.